Recent Updates on the Association Between Alzheimer’s Disease and Vascular Dementia - M. Ashraf, Ghulam; Chibber, Sandesh; Mohammad; K. Zaidi, Syed; Tabrez, Shams; Ahmad, Ausaf; Shakil, Shazi; Mushtaq, Gohar; S. Baeesa, Saleh; A. Kamal, Mohammad (Medicinal Chemistry, 2016)
The two most common forms of dementia are Alzheimer’s disease (AD) followed by vascular dementia (VaD), together accounting for a whopping 60-80% of total dementia cases worldwide. Even though these diseases are recognized as ‘common’, they still remain underdiagnosed. Recent research suggests that AD and VaD are closely intertwined. The symptoms of AD and VaD can be similar and the two conditions can occur simultaneously. A large number of patients diagnosed with AD have also been reported with VaD-caused brain damage. Moreover, both the diseases have been reported to have similar risk factors. The overlap between these diseases is important because the lifestyle changes and medications prescribed to curb one of these diseases may also help curb the other. In the present review, we present an inclusive outline of parallelism between AD and VaD by exploring the potential commonalities at the mechanistic and therapeutic levels.
Keywords: reactive oxygen species